Zinc Status in Febrile Seizure: A Case-Control Study - SALEHIOMRAN, MohammadReza; Masoumeh MAHZARI, Masumeh (Iranian Journal of Child Neurology, 2013)
How to Cite This Article: Salehiomran MR, Mahzari M. Zinc Status in Febrile Seizure: A Case-Control Study. Iran J Child Neurol. 2013 Autumn; 7(4):20-23. Objective Febrile seizure is the most common type of seizure in children. Their incidence is 2-5%. There are different hypotheses about relationship between neurotransmitters and trace elements (such as zinc) and febrile seizure. Zinc, as a major element of some enzymes, plays an important role in the central nervous system (CNS) and can affect some inhibitory mechanisms of CNS. The aim of the present study was to determine whether there were any changes in serum zinc level in children with febrile seizure in comparison with febrile children without seizure. Materials & Methods This case-control study was performed on 100 patients aged 6 months to 6 years. This study was conducted between January and August 2012, on 50 children with febrile seizures (case) and 50 febrile children without seizures (control), that were referred to Amirkola Children Hospital (a referral hospital in the north of Iran). Two groups were matched for age and sex. The serum zinc levels in the both groups were determined by atomic absorption spectrophotometry method. Results The mean serum zinc level was 0.585±0.166 mg/L and 0.704±0.179 mg/L in the case group and the control group, respectively (p=0.001). The mean serum zinc level was significantly lower in the febrile seizure group compared to the control groups. Conclusion Our findings revealed that serum zinc level was significantly lower in children with simple febrile seizure in comparison with febrile children without seizure. It can emphasize the hypothesis that there is a relation between serum zinc level and febrile seizure in children. References Varma RR. Febrile seizures. Indian J Pediatr 2002; 69(8); 697-700. Talebian A, Vakili Z, Talar SA, Kazemi M, Mousavi GA. Assessment of the relation between serum zinc and magnesium levels in children with febrile convulsion. Iranian j pathol 2009;4(4):157-60. Mollah MA, DEy PR, Tarafdar SA, Akhter S, Ahmed S, Hassan T, et al. Zinc in CSF of patients with febrile convulsion. Indian J Pediatr 2002;69(10):859-61. Auvichayapat P, Auvichayapat N, Jedsrisuparp A, Thinkhamrop B, Sriroj S, Piyakulmala T, et al. Incidence of febrile seizures in thalassemic patients. J Med Assoc Thai 2004;87(8):970-3. Nelson KB, Ellenberg JH. Prenatal and perinatal antecedents of febrile seizures. Ann Neurol 1990;27(2):127-31. Udani V.Pediatric epilepsy - An Indian perspective. Indian J Pediatr 2005; 72(4):309-13. Ehsanipour F, Talebi-Taher M, Harandi N, Kani k. Serum zinc level in children with febrile convulsion and its comparison with that of control group. Iranian J Pediatr 2009;199:65-8. Heydarian F, Ashrafzadeh F, Kam S. Simple febrile seizure: The role of serum sodium levels in prediction of seizure recurrence during the first 24 hours. Iran J Child Neurol 2009;3(2):31-4. Jun-Hwa Lee, Jeong Hyun Kim. Comparison of Serum Zinc Levels Measured by Inductively Coupled Plasma Mass Spectrometry in Preschool Children with Febrile and Afebrile Seizures. Ann Lab Med 2012;32(3):190-3. Heydarian F, Ashrafzadeh F, Ghasemian A. Serum zinc level in patient with simple febrile seizure. Iran J Child Neurol 2010;4(2):41-3. Garty B, Olomucki R, Lerman ST, Nitzan M. Cerebrospinal fluid zinc concentration in febrile convulsion. Arch Dis Child 1995;73(4):338-41. Daoud AS, Batieha A, Abu-Ekteish F, Gharaibeh N, Ajlouni S, HijaziS. Iron status: a possible risk factor for the first febrile seizure. Epilepsia 2002;43(7):740-3. Ganesh R, Janakiraman L, Meenakshi B. Serum zinc levels are low in children with simple febrile seizures compared with those in children with epileptic seizures and controls. Ann Trop Paediatr 2011;31(4):345-9. Cho WJ, Son BH, Kim SW. Levels of Sodium and Zinc concentration in febrile convulsion. Korean Child Neural Soc1999;7(2):214-9. Burtis carl A, Ashwood, Edwhard R; Brun, David E. Tietz fundamentals of clinical chemistry. 6th ed. Philadelphia: Saunders Elsevier; 2008. P. 505-7. Smart TG, Hosie AM, Miller PS. Zn2+ ions: modulators of excitatory and inhibitory synaptic activity. Neuroscientist 2004;10(5):432-4. Mollah MA, Rakshit SC, Anwer KS, Arslan MI, saha N, Ahmeds, et al. Zinc concentration in serum and cerebrospinal fluid simultaneously decrease in children with febrile seizure: Finding from a Prospective study in Bangladesh. Acta pediatr 2008;97(12):1707-11.